ANALISIS MANAGEMEN LABA PADA PERIODE PENAWARAN PERDANA SAHAM-SAHAM (INITIAL PUBLIC OFFERINGS) PERUSAHAAN BADAN USAHA MILIK NEGARA DAN PERUSAHAAN SWASTA - , Hartoyo Nugroho Adi ([Yogyakarta] : Universitas Gadjah Mada, 2012)
Aggressive and global business competition currently had strived management of State Owned Entrespises (SOEs) to be able to compete with private companies. Business expansion, which were planned by SOEs and private companies, has forced also management to take a policy for go public. Initial Public Offering (IPO) is the great moment for the go public companies, and this moment also is the good moment for management to show their existence. Therefore, it is not impossible that management who act as agent would probably do earnings management with some purpose. And the effect from this moment also is not impossible that there would be changed in their companiesâ performance. This research has shown that earning management and prefomance changing during IPO has actually happened in SOEs and private companies. Strong hypothesis that earnings management and performance changing happened during periode of IPO, which management has made earnings management before IPO and companies performance changing after IPO.